Recycled Keychain: Daur Ulang Tutup Botol Menjadi Gantungan Kunci (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Household plastic waste remains a serious challenge in urban environments, including Jl. Assofa II, Kebon Jeruk, West Jakarta, which is characterized by high population density and intense socio-economic activities. The low level of public awareness in sorting and managing plastic waste, particularly bottle caps, highlights the need for educational approaches from an early age. This community service activity aimed to enhance environmental awareness, creativity, and character development among children through the “Recycled Keychain” project, which involved recycling plastic bottle caps into keychains. The activity was implemented using a Project-Based Learning (PjBL) approach and involved 12 children aged 7–9 years as the main participants. The implementation methods included education on waste management based on the principles of reduce, reuse, and recycle (3R), collection and sorting of bottle caps, and the process of creating creative products. The results showed an increase in children’s environmental awareness and environmentally responsible behavior, the creation of eco-friendly educational products, as well as improvements in creativity, motor skills, and teamwork abilities. In addition, this activity supported the strengthening of the Pancasila Student Profile, particularly in the dimensions of cooperation, critical thinking, creativity, and independence. Overall, the Recycled Keychain project proved to be an effective model of contextual, participatory, and sustainable environmental education in instilling environmental care values from an early age in urban communities.